2017
DOI: 10.1186/s40900-017-0068-9
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a type 1 diabetes young adult patient and public involvement panel to develop a health behaviour change intervention: the D1 Now study

Abstract: Plain English summaryMany young adults with type 1 diabetes (T1D) find it hard to control their blood glucose levels. With lots of things going on in their lives, their diabetes is often not the most important thing to them. That means they do not always take care of their T1D, for example by going to clinic appointments. Young adults with T1D do not usually get the chance to make suggestions on how to improve diabetes services. Being involved could help young adults to shape the diabetes care services that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…This study will add to the evidence of how clinics should be restructured to be more responsive to the needs of this population and will inform the on‐going intervention that the D1 Now Study team are currently developing and evaluating. The findings will contribute to a multifaceted development approach to user‐centred development . Such development work has helped to inform core components of the D1 Now intervention.…”
Section: Resultsmentioning
confidence: 89%
“…This study will add to the evidence of how clinics should be restructured to be more responsive to the needs of this population and will inform the on‐going intervention that the D1 Now Study team are currently developing and evaluating. The findings will contribute to a multifaceted development approach to user‐centred development . Such development work has helped to inform core components of the D1 Now intervention.…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, we have been contacted by biomedical researchers and patient advocates from other disease areas for advice, which was a major catalyst for publishing the approach we used. We are now in the early stage of developing researcher training and evidence‐based approaches to public involvement of young people in biomedical research across all disciplines in association with the National Children's Research Centre.…”
Section: Future Directionsmentioning
confidence: 99%
“…The D1 Now study team has demonstrated that it is both feasible and desirable to include a PPI panel of young adults with T1D in health research 27,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Full details of the process of the formation of the YAP are published elsewhere 27 . The panel consisted of 8 young people aged between 18 and 25 years living with T1D who volunteered as co-researchers with the study team.…”
Section: Phase 1: Formation Of a Young Adult Panel (Yap)mentioning
confidence: 99%